Public Spending Efficiency in the OECD Benchmarking Health Care, Education and General Administration - Dutu, Richard (OECD Economics Department Working Papers, 2016)
In many OECD countries changes in demography and health conditions are putting pressure on public finance. To prevent further expansion of government spending as a percentage of GDP, public spending efficiency will need to be raised. This paper uses data envelopment analysis (DEA) to assess the efficiency of welfare spending in a sample of OECD countries around 2012, focussing on health care, secondary education and general public services. The DEA model has a two input-one output structure, with at least one of the variables representing a composite indicator controlling for country-specific factors (socio-economic environment and life-style factors, for example). We find wide dispersion in efficiency measures across OECD countries and provide possible quantified improvements for both output and input efficiency